2021
DOI: 10.1177/2325958220985665
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health in Women Living With HIV: The Unique and Unmet Needs

Abstract: Women living with HIV (WLWH) experience depression, anxiety, and posttraumatic stress symptoms at higher rates than their male counterparts and more often than HIV-unaffected women. These mental health issues affect not only the well-being and quality of life of WLWH, but have implications for HIV management and transmission prevention. Despite these ramifications, WLWH are under-treated for mental health concerns and they are underrepresented in the mental health treatment literature. In this review, we illus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 149 publications
3
82
1
3
Order By: Relevance
“…Pregnancy and the postpartum period are times of significant biological, social, and psychological changes for a woman and HIV adds another layer of complexity [ 7 9 ]. For WWH, pregnancy may be a time of increased psychological vulnerability due to different contextual factors, disclosure issues, and HIV-related stigma [ 6 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy and the postpartum period are times of significant biological, social, and psychological changes for a woman and HIV adds another layer of complexity [ 7 9 ]. For WWH, pregnancy may be a time of increased psychological vulnerability due to different contextual factors, disclosure issues, and HIV-related stigma [ 6 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy and the postpartum period are times of significant biological, social, and psychological changes for a woman and HIV adds another layer of complexity [ 7 9 ]. For WWH, pregnancy may be a time of increased psychological vulnerability due to different contextual factors, disclosure issues, and HIV-related stigma [ 6 , 9 , 10 ]. Moreover, in addition to the usual stresses of new motherhood, WWH must also cope with stressors that include their own health, the unknown infectious states of their infants, and attending to their infants´ unique needs such as the administration of prophylactic antiretroviral medication [ 6 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Women living with HIV (WLWH) have a higher burden of CMHD compared to women without HIV and men living with HIV. Mental health issues in WLWH, such as depression, posttraumatic stress (PTSD), and anxiety, are associated with poor quality of life and worse HIV health outcomes [ 4 ]. Mental health symptoms, particularly depression, and mental health vulnerabilities are also widespread among pregnant WLWH and have the potential to affect well-being, quality of life, and clinical obstetric outcomes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, HIV is a major problem among the youth especially among females [34]. Other studies have also found a higher prevalence of psychological distress among women living with HIV compared to men [35][36][37]. It is likely therefore that differential patterns of exposure to HIV predispose these population groups to psychological distress.…”
Section: Discussionmentioning
confidence: 99%